Not Just Loss-of-Function Variations: Identification of a Hypermorphic Variant in a Patient With a CDKL5 Missense Substitution. (9th April 2022) - Frasca, Angelisa; Pavlidou, Efterpi; Bizzotto, Matteo; Gao, Yunan; Balestra, Dario; Pinotti, Mirko; Dahl, Hans Atli; Mazarakis, Nicholas D.; Landsberger, Nicoletta; Kinali, Maria
Abstract : Background and Objectives: CDKL5 deficiency disorder (CDD) is a neurodevelopmental encephalopathy characterized by early-onset epilepsy and impaired psychomotor development. Variations in the X-linked CDKL5 gene coding for a kinase cause CDD. Molecular genetics has proved that almost all pathogenic missense substitutions localize in the N-terminal catalytic domain, therefore underlining the importance for brain development and functioning of the kinase activity. CDKL5 also features a long C-terminal domain that acts as negative regulator of the enzymatic activity and modulates its subcellular distribution. CDD is generally attributed to loss-of-function variations, whereas the clinical consequences of increased CDKL5 activity remain uncertain. We have identified a female patient characterized by mild epilepsy and neurologic symptoms, harboring a novel c.2873C>G nucleotide substitution, leading to the missense variant p.(Thr958Arg). To increase our comprehension of genetic variants in CDKL5 -associated neurologic disorders, we have characterized the molecular consequences of the identified substitution. Methods: MRI and video EEG telemetry were used to describe brain activity and capture seizure. The Bayley III test was used to evaluate the patient development. Reverse transcriptase PCR was used to analyze whether the identified nucleotide variant affects messenger RNA stability and/or splicing. The X chromosome inactivation pattern was analyzed determining the DNA methylation status of the androgen receptor ( AR ) gene and by sequencing of expressed alleles. Western blotting was used to investigate whether the novel Thr958Arg substitution affects the stability and/or enzymatic activity of CDKL5. Immunofluorescence was used to define whether CDKL5 subcellular distribution is affected by the Thr958Arg substitution. Results: Our data suggested that the proband tends toward a skewed X chromosome inactivation pattern in favor of the novel variant. The molecular investigation revealed that the p.(Thr958Arg) substitution leads to a significant increase in the autophosphorylation of both the TEY motif and residue Tyr 171 of CDKL5, as well as in the phosphorylation of the target protein MAP1S, indicating an hyperactivation of CDKL5. This occurs without evidently affecting the kinase subcellular distribution. Discussion: Our data provide a strong indication that the c.2873C>G nucleotide substitution represents an hypermorphic pathogenic variation of CDKL5, therefore highlighting the importance of a tight control of CDKL5 activity in the brain.